Determinan Kinerja Anggaran pada Organisasi Perangkat Daerah - Syukriy Abdullah; Afrah Junita (Akuntabilitas, 2020)
Budget performance is the basis for evaluating and assessing the quality of financial management and budgeting in government organizations, especially in local government’s agencies. The purpose of this study is to examine the effect of budget size (TB), budget change (PB), and previous year budget variance (VS) on budget performance (KA) at agencies of Gayo Lues Regency. The sample in this study amounted to 44 work units of regional apparatus (SKPD) for fiscal year 2016-2017. Data analysis using multiple linear regression model. The results show that PB has no effect on KA, while TB and VS have negative effect on KA